1994
DOI: 10.1128/jb.176.18.5673-5680.1994
|View full text |Cite
|
Sign up to set email alerts
|

Multiple copies of the proB gene enhance degS-dependent extracellular protease production in Bacillus subtilis

Abstract: Bacillus subtilis secretes extracellular proteases whose production is positively regulated by a two-component regulatory system, DegS-DegU, and other regulatory factors including DegR. To identify an additional regulatory gene(s) for exoprotease production, we performed a shotgun cloning in the cell carrying multiple copies of degR and found a transformant producing large amounts of the exoproteases. The plasmid in this transformant, pLC1, showed a synergistic effect with multiple copies of degR on the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 51 publications
1
49
1
Order By: Relevance
“…After addition of sodium chloride to the medium, B. subtilis cells were shown to accumulate proline (34). Moreover, Ogura and coworkers (26) showed that the presence of multiple copies of the proB gene, which is required for proline biosynthesis, led to enhanced aprE expression. The authors suggested that the proB gene product, ␥-glutamyl phosphate, could serve as a phosphodonor, leading to phosphorylation of DegS and to stimulation of degradative enzyme synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…After addition of sodium chloride to the medium, B. subtilis cells were shown to accumulate proline (34). Moreover, Ogura and coworkers (26) showed that the presence of multiple copies of the proB gene, which is required for proline biosynthesis, led to enhanced aprE expression. The authors suggested that the proB gene product, ␥-glutamyl phosphate, could serve as a phosphodonor, leading to phosphorylation of DegS and to stimulation of degradative enzyme synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence comparison with the databases were performed using BLAST through the NCBI E-mail server [18]. Protein secondary structure analysis was determined by using the PredictProtein program (EMBL Heidelberg, Germany) [19,20] with multiple sequence alignments of the seven proteins showing highest similarity, P5CS from V. aconitifolia [8], y-glutamyl kinase and y-glutamyl phosphate reductase from E. coli [13], S. marcescens [14] and Bacillus subtilis [21]. Inclusion of protein homologs increases the prediction accuracy of the secondary structure to 70% [19].…”
Section: Dna and Protein Sequence Analysismentioning
confidence: 99%
“…Strain JSB11 [D(proBA : : cat)1] was isolated after transformation of strain JH642 with DNA of plasmid pJS8 (linearized with the restriction enzymes BamHI and EcoRI) and subsequent selection for chloramphenicol-resistant transformants. Strain JSB17 [proA6pEPV1T (tet)] was isolated after transformation of strain JH642 with the circular plasmid pEPV1T (Ogura et al, 1994) and selection for tetracycline-resistant colonies; in this strain, plasmid pEPV1T is inserted into the proA gene via a Campbell-type single-crossover integration event, thereby disrupting the integrity of proA. The proA mutation present in strain JSB17 was introduced into strain FSB1 [(treA : : neo)1] (Spiegelhalter & Bremer, 1998) by DNA transformation with chromosomal DNA from strain JSB17 and subsequent selection for tetracycline-resistant colonies.…”
Section: Methodsmentioning
confidence: 99%